Successful controlled ovarian stimulation despite elevated hCG levels after first-trimester abortion in the context of fertility preservation. (November 2013) - Goeckenjan, M.; Rösner, S.; Toth, B.; Strowitzki, T.; Germeyer, A.
Abstract Fertility preservation prior to gonadotoxic chemotherapy by cryopreservation of the ovarian tissue and controlled ovarian stimulation can be effective immediately after induced abortion in the first trimenon. In a reproductive endocrinology and infertility unit of a tertiary care university-based medical centre (University Hospital of Heidelberg) a 37-year-old women with breast cancer was counseled for fertility preservation. Cryopreservation of ovarian tissue, followed by ovarian stimulation for planned intracytoplasmatic sperm injection (ICSI), transvaginal oocyte aspiration and cryopreservation of fertilized eggs was performed in spite of persistently elevated human chorionic gonadotropin (hCG)-levels after induced abortion. Twenty-four fertilized oocytes with a fertilization rate of 92% were cryopreserved. Ovarian stimulation and oocyte cryopreservation can be successfully performed with good results immediately after miscarriage, despite persistent high hCG-levels.